2014
DOI: 10.1007/s10811-014-0483-3
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal cell disruption by hydrodynamic cavitation for the production of biofuels

Abstract: Cell disruption is an essential pre-treatment for the efficient extraction of many types of intracellular metabolites such as proteins, carbohydrates, DNAs or lipids; but the high process energy requirement becomes an important issue for low valued commodities such as biofuels. Current mechanical cell disruption methods such as high-pressure homogeniser or sonication require energy input in the order of hundreds of MJ kg −1 of the dry mass; in addition, these methods do not have the capacity suitable for biofu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 37 publications
0
17
0
3
Order By: Relevance
“…The production of renewable energy resources such as biodiesel and biogas via the complex treatment of cyanobacteria biomass is a sustainable strategy. HC-based technologies can increase the efficiency of inedible fat extraction [92], since cell disruption is mainly restrained to the cell wall and membrane [9]. Given its energy efficiency, comparable extractability, and scale-up potential, HC may become an industrial-scale method for microalgae extraction [21].…”
Section: Lipid Extraction From Microorganismsmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of renewable energy resources such as biodiesel and biogas via the complex treatment of cyanobacteria biomass is a sustainable strategy. HC-based technologies can increase the efficiency of inedible fat extraction [92], since cell disruption is mainly restrained to the cell wall and membrane [9]. Given its energy efficiency, comparable extractability, and scale-up potential, HC may become an industrial-scale method for microalgae extraction [21].…”
Section: Lipid Extraction From Microorganismsmentioning
confidence: 99%
“…As a result, HCR was shown to have 3 MJ/kg of specific energy consumption, indicating that HCR is much more efficient than UAE. Although HC can sufficiently injure the cell wall to leave solvents diffusion for lipid extraction, it still accounts for about 13% of the total biomass energy, which is too high for the biofuels production [9]. Similarly, lipids in microalgae Nannochloropsis sp.…”
Section: Lipid Extraction From Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrodynamic cavitation that was used to cell disruption technique was investigated, with the level of cell disruption was determined by lipids extracted and chlorophyll released. It was found that for lipids extraction, hydrodynamic cavitation technique was requiring energy as big as 3 MJ/kg with the microalgae concentration 1.5-2% w/w [18]. Hydrodynamic cavitation to assist lipid extraction simultaneously from Nannochloropsis Salina sp.…”
Section: Introductionmentioning
confidence: 99%
“…For cell disintegration, the most common methods include bead milling (chapter 2-5), homogenization (Safi et al, 2014a), high-voltage electric discharges (Zhang et al, 2018), pulsed electric fields and ultrasounds (Grimi et al, 2014;Parniakov et al, 2015), thermal processing and microwaves (Jazrawi et al, 2015;Passos et al, 2015), chemical and enzymatic hydrolysis (Safi et al, 2017a;Sari et al, 2015) and dissolution using ionic liquids (Desai et al, 2016a;Fujita et al, 2013;Teixeira, 2012). Other innovative technologies have been proposed, among which hydrodynamic cavitation (Lee et al, 2015), microfluidization (Cha et al, 2012) and explosive decompression (Lorente et al, 2018;Phong et al, 2018b;Gunerken et al, 2019).…”
Section: Unit Operations Dimensionmentioning
confidence: 99%